Marine theme playground for neighborhood kids - Ghosh, Ayan (2023)
One of the latest additions to community spaces around the Banganga Tank is this marine-themed playground adjacent to Rameshwar Temple. This site was earlier used as a garbage dumping ground before it was revamped by the RPG Foundation as part of the Banganga Revival Project and is now a place of fun and games for the neighborhood kids.